PKA mediates modality-specific modulation of the mechanically gated ion channel PIEZO2 - Meyer, Irina; Verkest, Clement; Vespermann, Lucas; Mair, Thomas; Voß, Hannah; Zeitzschel, Nadja; Lechner, Stefan G. (The journal of biological chemistry, 2023)
PKA is a downstream effector of many inflammatory mediators that induce pain hypersensitivity by increasing the mechanosensitivity of nociceptive sensory afferent. Here, we examine the molecular mechanism underlying PKA-dependent modulation of the mechanically activated ion channel PIEZO2, which confers mechanosensitivity to many nociceptors. Using phosphorylation site prediction algorithms, we identified multiple putative and highly conserved PKA phosphorylation sites located on intracellular intrinsically disordered regions of PIEZO2. Site-directed mutagenesis and patch-clamp recordings showed that substitution of one or multiple putative PKA sites within a single intracellular domain does not alter PKA-induced PIEZO2 sensitization, whereas mutation of a combination of nine putative sites located on four different intracellular regions completely abolishes PKA-dependent PIEZO2 modulation, though it remains unclear whether all or just some of these nine sites are required. By demonstrating that PIEZO1 is not modulated by PKA, our data also reveal a previously unrecognized functional difference between PIEZO1 and PIEZO2. Moreover, by demonstrating that PKA only modulates PIEZO2 currents evoked by focal mechanical indentation of the cell, but not currents evoked by pressure-induced membrane stretch, we provide evidence suggesting that PIEZO2 is a polymodal mechanosensor that engages different protein domains for detecting different types of mechanical stimuli.
Online verfügbar 4 May 2023, Version des Artikels 3 June 2023
Gesehen am 18.09.2023